Treasure on the Shelves and the Stage Longs for New Plays and Playwrights - Appiah-Adjei, D. (School of Performing Arts, University of Ghana, Legon, 2015)
This paper examines how playwrights, especially, playwriting majors from the Department of Theatre Arts, School of Performing Arts, University of Ghana, Legon have had their plays kept on the shelves in the library and departmental offices. It is also to ascertain whether some of the plays have ever been staged or not. Based on documentation theory, the objective of this paper is to discover and put on record the number of playwrights and their produced plays from 1980 to 2014. The study is basically Qualitative Methodology; a library research, one-on-one, and group informal conversation with some lecturers, students, both past and present, of the Department of Theatre Arts, and personal observations. In the end, it was discovered that four (4) out of seventy (72) plays identified have been produced for an audience. The paper, therefore, presents the clear picture of “artistic waste”, and makes recommendations for the School authorities to encourage prospective directing students to endeavor and direct some of the potential scripts for their practical.
Keywords: Treasure; The Shelves; The Stage; New Plays; Playwright; Documentation Theory